(3cGed GdUfGYI aj GdaQhSjI hGdTLGYIs
(3ChdgG (B:s
(3GdMeO ddg GdPi CPgH YfG GdMRf bGd GdeDda YaG Gddg Yfg Efi de CRd HYO Cf hgH Gddg di ef GdeYQaI ai CHhGH GdMQhH HeG jMJGL Edjg GdYed HGdSjha s
(3BNQgG (B:s
(3aJWYfg BefG ef QeMg Ke JNQL efg QjYkG hGddg CYde HGdUhGH hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(5 / 32 (3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs